Heterogeneity in displacement exposure of migrants in Shenzhen, China. Issue 15 (18th November 2018) - Liu, Ying; Geertman, Stan; Lin, Yanliu; van Oort, Frank
ABSTRACT: Large-scale residential displacement is occurring in many Chinese cities, with migrants living in 'Villages in the City' (ViCs) as the main groups affected. This study uniquely captures a situation in Baishizhou village in Shenzhen, where people live under a threat of imminent displacement. We elucidate the (social) heterogeneity of the affected population, their perceptions before and residential choices after displacement. Identifying four migrant groups, the two older generation groups (the first-generation labour migrant class and the new affluent migrant class) tend to anticipate severe consequences more than the two younger generation groups (the second-generation labour migrant class and the intellectual migrant class), mainly because the former groups are more economically and emotionally attached to the village. The residential choices of migrants (of all types) facing displacement increase housing demand in (remaining) ViCs in central urban areas, causing limitations to the absorptive capacity of cities for displaced migrants. Displacement occasionally enables displacees to climb the housing ladder; however, more often, it drives them further away from the city and places of work.